Fzd3 Expression Within Inner Ear Afferent Neurons Is Necessary for Central Pathfinding - Stoner, Zachary A.; Ketchum, Elizabeth M.; Sheltz-Kempf, Sydney; Blinkiewicz, Paige V.; Elliott, Karen L.; Duncan, Jeremy S. (Frontiers in Neuroscience, 2022)
During development the afferent neurons of the inner ear make precise wiring decisions in the hindbrain reflective of their topographic distribution in the periphery. This is critical for the formation of sensory maps capable of faithfully processing both auditory and vestibular input. Disorganized central projections of inner ear afferents in Fzd3 null mice indicate Wnt/PCP signaling may be involved in this process and ear transplantation in Xenopus indicates that Fzd3 is necessary in the ear but not the hindbrain for proper afferent navigation. However, it remains unclear in which cell type of the inner ear Fzd3 expression is influencing the guidance of inner ear afferents to their proper synaptic targets in the hindbrain. We utilized Atoh1-cre and Neurod1-cre mouse lines to conditionally knockout Fzd3 within the mechanosensory hair cells of the organ of Corti and within the inner ear afferents, respectively. Following conditional deletion of Fzd3 within the hair cells, the central topographic distribution of inner ear afferents was maintained with no gross morphological defects. In contrast, conditional deletion of Fzd3 within inner ear afferents leads to central pathfinding defects of both cochlear and vestibular afferents. Here, we show that Fzd3 is acting in a cell autonomous manner within inner ear afferents to regulate central pathfinding within the hindbrain.